Upper Silurian (late Ludlovian) to upper Devonian (Frasnian ?) stratigraphy and depositional history of the Vendom fiord region, Ellesmere Island, Canadian Arctic ... - Roblesky, Robert F. (University of Calgary, 1979)
Bibliography: p. 174-188. ...